ENGINEERING ECONOMICS OF GREEN INFRASTRUCTURE INVESTMENT - Shakhrizoda Sirojiddinovna Olimova (European Science Publishing, 2025)
The article explores the transformation of engineering economics in the era of the global energy transition. It argues that traditional cost–benefit analysis is no longer sufficient to evaluate large-scale infrastructure projects under conditions of technological change, policy uncertainty, and environmental constraints. Based on recent data from the International Energy Agency (IEA), International Renewable Energy Agency, IMF, OECD, and UNEP, the study shows that clean-energy investment has become the dominant form of capital allocation worldwide. It concludes that engineering economics now functions as a governance tool—linking micro-level investment decisions to long-term sustainability and resilience goals.
Keywords: Engineering economics; green infrastructure; clean energy investment; life-cycle cost analysis; discount rate; risk assessment; sustainability; renewable energy; innovation finance; energy transition.